2003
DOI: 10.1021/jm021120f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure−Activity Studies of Novel Orally Active Non-Terpenoic 2,3-Oxidosqualene Cyclase Inhibitors

Abstract: New orally active non-terpenoic inhibitors of human 2,3-oxidosqualene cyclase (hOSC) are reported. The starting point for the optimization process was a set of compounds derived from a fungicide project, which in addition to showing high affinity for OSC from Candida albicans showed also high affinity for human OSC. Common structural elements of these inhibitors are an amine residue and an electrophilic carbonyl C atom embedded in a benzophenone system, which are at a distance of about 10.7 A. Considering that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 48 publications
1
54
0
Order By: Relevance
“…Inhibitors have been designed considering that the most known effective inhibitors of enzymes belonging to the family of squalene and oxidosqualene cyclases share a structure consisting in two well characterized moieties: a moiety bearing a properly shaped tertiary amino function capable of interacting with a catalytically critical Asp455 residue (human numbering) of the enzyme [4,32], and a moiety shaped so as to productively interact with the aromatic residues of the active site. The latter moiety is an isoprenic structure mimicking the squalene skeleton in azasqualene derivatives [26,33], whereas in other series of inhibitors is an electron-deficient aromatic system [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inhibitors have been designed considering that the most known effective inhibitors of enzymes belonging to the family of squalene and oxidosqualene cyclases share a structure consisting in two well characterized moieties: a moiety bearing a properly shaped tertiary amino function capable of interacting with a catalytically critical Asp455 residue (human numbering) of the enzyme [4,32], and a moiety shaped so as to productively interact with the aromatic residues of the active site. The latter moiety is an isoprenic structure mimicking the squalene skeleton in azasqualene derivatives [26,33], whereas in other series of inhibitors is an electron-deficient aromatic system [4].…”
Section: Discussionmentioning
confidence: 99%
“…The latter moiety is an isoprenic structure mimicking the squalene skeleton in azasqualene derivatives [26,33], whereas in other series of inhibitors is an electron-deficient aromatic system [4]. Crystallographic studies carried on both squalene-hopene cyclase from Alicyclobacillus acidocaldarious and human OSC provided excellent explanations of the inhibitory properties of different compounds bearing an amino function [4,7,32,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22) SHC may therefore be used as a model to predict how newly designed inhibitors may interact with OSCs. Recently, the interaction of several new inhibitors of human OSC 17) with the active site of SHC was investigated by co-crystallization experiments. 23) Because comparative studies on the two enzyme types 24,25) have shown close correspondence of their inhibitor activities, we recently investigated a group of meroterpenoids that proved to be excellent inhibitors of SHC.…”
mentioning
confidence: 99%